(untitled) (Journal of Engineering, 2010)
The present work is concerned with the theoretical and experimental investigation of flow pattern of Newtonian fluid in liquid mixing process in stirred tank with flat blade impeller. A threedimensional model for mixing process was simulated. The effected parameters are rotation speed and impeller diameter. Continuity, momentum, and turbulent equations were solved by ANSYS package software 5.4 code with FLOTRAN/CFD based on Finite Element method. In the experimental work, two visualization methods are used in this work, the first method is the acidbase reaction visualization method and the second is the particle distribution visualization method. Different chemical materials were used in the first method, NaOH as a base, 2 4 H SO as acid and Methyl red as indicator, while polymer particles were used in the second method. The results of 3D model showed that the speed rotation directly affected the mixing zones, where the speed reduction by half decreasing the mixing zones approximately by half. Also the impeller diameter increasing clearly affected the mixing process where the mixing zones concentrated directly above and below the impeller. In the experimental work, the acid-base reaction visualization method showed that the mixing zones decreased due to the rotation speed reduction depend on the red and yellow colors, which describe the good mixing and poor mixing zones respectively. The mixing zones were concentrated directly above and below the impeller due to the impeller diameter increasing,. The particles distribution method showed that the mixing zones decreased due to the speed reduction, while the mixing zones concentrated directly above and below the impeller due to the impeller diameter increasing. The results showed a good agreement between the theoretical and experimental works in studying the effect of rotating speed, and impeller diameter .